2023
DOI: 10.1186/s40168-023-01497-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic bacterial consortia transplantation for the treatment of Gardnerella vaginalis-induced bacterial vaginosis in mice

Abstract: Bacterial vaginosis (BV) is a disease caused by vaginal microbiota dysbiosis. Here, we propose the use of synthetic bacterial consortia transplantation (SBCT) for the treatment of Gardnerella vaginalis-induced BV mice. The results showed that SBCT significantly reduced vaginal tissue damage and restored the vaginal microbiota, decreased the secretion of pro-inflammatory cytokines (IL-1β and IL-8), and suppressed NF-κB activation. IL-17, iNOS, and COX-2 expression in vaginal tissue were also down-regulated. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Numerous studies have investigated the association between vaginal microbes and vaginal atrophy. They have used VMT to treat vaginal microecological imbalances [19]. However, there is a lack of re-search on the role of vaginal microbes in improving vaginal atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have investigated the association between vaginal microbes and vaginal atrophy. They have used VMT to treat vaginal microecological imbalances [19]. However, there is a lack of re-search on the role of vaginal microbes in improving vaginal atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…The overall microbial community composition was more complex in SUI group. Microbial dysbiosis was observed [23,24] (Figure 2B). Based on the proportion of samples with dysbiosis of the vaginal microbiota in two groups (whether the vaginal ora is dominated by Lactobacillus).…”
Section: The Composition and Biomarkers Of The Vaginal Microbiotamentioning
confidence: 99%
“…The findings revealed that SBCT effectively mitigated vaginal tissue damage, rebalanced the vaginal microbiota, and decreased the release of pro-inflammatory cytokines like IL-1b and IL-8. Furthermore, SBCT inhibited NF-jB activation and reduced the expression of IL-17, iNOS, and COX-2 in vaginal tissues [87]. Tilapia piscidin 4 (TP4)-an antimicrobial peptide from Nile tilapia-has a broad antibacterial activity, its potential role in modulating macrophage response during BV was not understood [88].…”
Section: Bv Treatment Prognosis: Insights From Cytokine Dynamicsmentioning
confidence: 99%